Diagnóstico y estimación de costos de prevención y evaluación para mejorar el proceso de dulces en el Regocijo de Calceta - Cabal Muñoz, Mariuxi Maribel (2014)
This research was conducted with goal of diagnosing failures that affect the processes of development and production of sweets in the microenterprise El Regocijo , which is the main objective of this work , in this process the specific objectives were developed such as: Development of the referential theoretical framework to support the subject under study, backing itself in events of historical research to apply it according to their needs ; design tool of diagnosis, management mechanisms such as dynamic indicators were established to meet historical sales through the development of production , plus the efficiency of process management are analyzed assorted sweets , which refers to appraisal costs and prevention in every activity of the reflected process through flow chart where faults are determined by the diagram Pareto , and cause and effect is applied , finally proposed and socialized improvement actions to legal representative microenterprise to know the importance of the process to monitor time and therefore also the implementation of technological equipment to enable performance with the exact heavy feedstock avoiding waste and reducing costs. For the development of research was used as the interview technique addressed to the owner of Exhilaration, Mrs. Damarys Loor, aiming to collect information on the management and production company.